TINDAK PERLOKUSI DALAM LIRIK-LIRIK LAGU POP KARYA COLDPLAY - PAILAHA, VIBRAINDI BETRAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This Research is an attempt to identify and analyze the perlocutionary act in Coldplay hit song lyrics. The collected data have been identified by using Leechâ€™s concept about the kind of the aspect of perlocutionary act and then analyzed them descriptively in terms of how the aspect of perlocutionary acts revealed by the speaker in the songs. The method which is used in this research is descriptive method. In collect data, the writer focused on identifying the aspect of perlocutionary act found in each lyrics of the songs. The Result shows that in terms of identified and analyzed the aspect of perlocutionary act. The writer found some aspect of perlocutionary act such as, bring hearer to know, persuade, amuse, get the hearer to do, and get the the hearer to think wheres the other aspect of perlocutioary act such as encourage, irritate, and relieve tension did not find in Coldplays hit songs lyrics. Â Key words : Perlocutionary Aspect, Hit Songs of Coldplay, Pragmatic Studi